Analysis of NRAS gain in 657 patients with melanoma and evaluation of its sensitivity to a MEK inhibitor. (January 2018) - Yan, Junya; Wu, Xiaowen; Yu, Jiayi; Yu, Huan; Xu, Tianxiao; Brown, Kevin M.; Bai, Xue; Dai, Jie; Ma, Meng; Tang, Huan; Si, Lu; Chi, Zhihong; et al.
Abstract: Background: Neuroblastoma rat-sarcoma ( NRAS ) mutations have been described in Chinese patients with melanoma. However, the status and the clinical significance of NRAS gain have not been investigated on a large scale. Methods: A total of 657 melanoma samples were included in the study. NRAS copy number was examined using the QuantiGene Plex DNA assay. The sensitivities of cell lines and patient-derived xenograft (PDX) models containing NRAS gain to a MAP/ERK kinase (MEK) inhibitor (binimetinib) were also evaluated. Results: The overall incidence of NRAS gain was 14.0% (92 of 657). Incidence of NRAS gain in acral, mucosal, chronic sun-induced damage (CSD) and non-CSD melanomas was 12.2%, 15.8%, 9.5% and 19.4%, respectively. NRAS gain was mutually exclusive to NRAS mutations ( P = 0.036). The median survival time for melanoma patients with NRAS gain was significantly shorter than that for patients with normal NRAS copy number ( P = 0.006). For patients containing NRAS gain, the median survival time for higher copy number (>4 copies) was significantly shorter than those with lower copy number (2–4 copies; P = 0.002). The MEK inhibitor (binimetinib) inhibited the proliferation of melanoma cells and the tumour growth of PDX models with NRAS gain. Conclusions: NRAS gain is frequent in patients with melanoma and may predict a poor prognosis of melanoma. The melanoma cells and PDX models containing NRAS gain are sensitive to MEK inhibitor (binimetinib), indicating that NRAS gain might be a new therapeutic target for melanoma. Highlights: We examine the copy number of NRAS in 657 cases of melanomas. NRAS gain occurs in 14% of Chinese melanoma patients and is associated with a poor prognosis of melanomas. The growth of melanoma containing NRAS gain was inhibited using binimetinib (an MAP/ERK kinase inhibitor) in vitro and in vivo .